Predictors of adherence following the theory of planned behavior among adult women availing oral contraceptive pills in public and private facilities in the City of Manila - Hernandez, Samantha Nicole C.; Guevarra, Niel Joules Y.; Ngo, Frances Lois U.; Roque, Chariz Ann Joy E. (Manila College of Pharmacy, University of the Philippines Manila, 2025)
Oral Contraceptive Pills (OCPs) are the most used form of contraception among women in the Philippines. However, poor adherence to this contraceptive method is widely observed, which has led to unintended pregnancies in the City of Manila. This study aims to identify the predictors of adherence following the Theory of Planned Behavior (TPB) among adult women availing OCPs in primary care facilities (PCFs) and private pharmacies in the City of Manila. This is a cross-sectional quantitative study using an interviewer-guided questionnaire in 26 randomized participants from PCFs and private pharmacies. A modified TPB and five-item MARS-5 questionnaire were employed. Data was analyzed using frequency statistics, multiple linear regression and logistic regression. Majority of adult users recognize that attitude (5.98 ± 0.99), subjective norm (5.73 ± 1.55), perceived behavioral control (PBC) (6.20 ± 0.79), and intention (6.59 ± 0.81) are behavioral factors to their adherence to OCPs. Most participants reported good adherence with 92.30% characterized as high adherers. Further, positive attitude towards OCP adherence (p=0.009) and strong PBC (p=0.012) were predictors of a participant’s intention to adhere to their OCP. In contrast, the subjective norm did not influence adherence (p=0.258). Personal autonomy is a prominent indicator of contraceptive use, however, a woman’s intention to use contraceptives does not necessarily increase adherence. Therefore, motivation alone cannot ensure adherence and interventions should focus on strengthening the self-efficacy of OCP users.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Contraceptives -- Utilization -- Health behavior -- Philippines; Oral contraceptives -- Patient adherence -- Predictive factors -- Philippines; Theory of planned behavior -- Application -- Women’s reproductive health -- Philippines